Evaluation of serum levels of nitric oxide in chemical victims of Sardsht 20 years after sulfure mustard exposure - T. Ghazanfari; R. Yaraee; Z. KiaSalari; F. Hedayati; H. Ghasemi; Sh. PourFarzam; M.R. Soroush; S. Faghihzadeh (Afarand Scholarly Publishing Institute, 2009)
Background: SM affects on multiple organs in the long term that causes different complications especially in eyes, skin and lung. It seems immune and inflammatory responses are involved in clinical manifestations. Nitric oxide (NO) is one of the important molecules in inflammation. The purpose of the study was to assess the serum levels of NO in chemical victims 20 years after exposure to SM in compare with unexposed group. Materials and Methods: This research has been carried out as historical cohort on 500 participants including 372 participants exposed to SM from Sardasht and 128 participants from Rabat. All participants of two groups have been examined by ophthalmologist, dermatologist and internist and then divided to normal group and with eye, skin, and lung problems groups. At the same time a specimen of peripheral venous blood was collected to evaluate serum level of NO by Greiss reaction. Results: Nine patients of control and 76 patients of exposed have had eye problems, 114 patients of control and 257 patients of exposed have had skin problems, 39 patients of control and 157 patients of exposed have had lung problems. This study showed that there was not any statistically significant difference between exposed and control groups in the average serum level of NO. There was not any relationship between serum level of NO and lung and eye problems and assessment showed that serum level of nitric oxide in exposed group without eye or lung problems was more than control group without eye or lung problems. In the assessment of skin problems there was a relationship between serum levels of NO and skin problems. The serum level of NO in the exposed group with skin problems was more than exposed group without skin problems. Conclusion: it has been found that by increasing of serum level of NO, the severity of skin lesions in chemical victims has been increased. As noticed by several complications in the chemical victims, more evaluation for the role of nitric oxide and changing of its systemic and local level in presenting different complication should be done.